Exergy optimization of HVAC with air recirculation - Chacón Chauca, Justo Antonio (2020)
In the next pages, an energetic and exergetic analysis of one specific Heat, Ventilation and Air Conditioning (HVAC) system, using air recirculation, will be detailed. Different operating conditions will be presented and the ones of least exergy destruction will be highlighted and analyzed. Both the first and second law of thermodynamics are used to understand and describe these phenomena through a specific performance criterion called Duty Specific Exergy Consumption1, noted DSExC in the rest. The main results presented in this document have been published in a peer-reviewed French journal dedicated to HVAC systems, see (Chacon Chauca, Quintanilla Munoz, & Vaudrey, 2019).